Motif Tanggung Jawab Sosial Lembaga Keuangan Mikro Syariah dalam Perspektif Ekonomi Syariah - Syaichoni, Ahmad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The primary issue addressed in the text is the importance of corporate governance, specifically within Sharia microfinance institutions, in achieving profitability and success. The study emphasizes the role of market share as an indicator of operational success for Sharia microfinance institutions, with a focus on meeting the needs of small communities. This study uses the library research method by extracting data from primary sources such as economics books and Sharia microfinance institutions. Data analysis is carried out using critical analysis and content analysis. The research findings highlight that these institutions use corporate social responsibility (CSR) as a strategic tool to promote their products and services. This, in turn, contributes to an increase in market share by introducing the company to the public. The text suggests that the implementation of CSR by Sharia microfinance institutions is motivated not only by economic considerations, such as marketing and promoting products but also by social motives, including a desire to assist others. In the context of Islamic or Sharia-compliant finance, the study underscores the integration of economic activities with ethical and socially responsible principles. The economic motive is evident in the use of CSR as a marketing tool to reach a wider community and promote financial products. The findings suggest that in the pursuit of economic goals, Sharia microfinance institutions also align themselves with social values by engaging in activities that benefit the broader community. This dual motive reflects the unique intersection of economic and ethical considerations within the framework of Sharia-compliant financial practices.